Waqf potentials as a relief tool during Covid-19 lockdown in Lagos, Nigeria - Zakariyah, Yushau; Zakariyah, Habeebullah; Mohd Noor, Azman (2020)
The foundational principle of Islam is Rahman and the beloved Prophet of Islam (peace be upon him) has been sent as rahmatan Lil Alamin, mercy to all mankind. It is upon this principle that Islam incorporates different pro-grams that will make life comfortable for all mankind. These kinds of pro-grams include Sadaqah, Zakat, and by extension Waqf. The latter has been used in many countries such as Malaysia, Turkey, Kuwait, etc as a way of al-leviating poverty, bridging the socio-economic gap, and empower masses es-pecially the vulnerable. As the whole world was unexpectedly sparked by the novel pandemic, COVID 19, every country has been on toe not only to pro-tect her habitants and city but also to render assistance on the basic needs. Some countries like Nigeria have been overwhelmed in successfully carrying out this task. They become "lone wolf" in this situation. This paper assesses how the pandemic affects the livelihood of people in Lagos state in Nigeria and the reliefs provided by the government to help the situation. It is thus revealed that Lagos State has the highest number of coronavirus cases with more than ten thousand cases. The pandemic affected the source of income of people and everyone finds it difficult to meet ends meet. The government has supported people through cash transfer and food distribution. However, it is found that the government alone was on the ‘battlefield’ making the matter complicated and the relief provided insubstantial. It is on this base that this study recommends creation of Waqf institution to provide comple-mentary role in such situation and beyond